DEBRIDEMENT SEBAGAI TATALAKSANA ULKUS KAKI DIABETIK - Made Agustya Darmaputra Wesnawa (E-Jurnal Medika Udayana, 2014)
Reported a case of female patient 45 years old with diagnose Diabetes Mellitus Type 2 withDiabetic Foot Ulcer Wagner grade 2 at region pedis dextra. Debridement was done in thispatient. The type of debridement was surgical debridement. The purpose of this procedure is toremove necrotic tissue and hyperkeratosis until reach the health tissue. After debridement, thewound was dressed with kassa sterile and elastic bandage. During treatment, there were no pus,bleeding, and unpleasant odor on wound, granulation tissue begin to appear, and pain on thepedis was reduced.